Answers

2016-04-23T23:52:30+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
9x²  - 15x + 6  = 0

Step 1. divide all terms by 9 ⇒ x² - 1.67x + 0.67 = 0
Step 2. move number term to the right side of the equation
x² - 1.67x = -0.67 
Step 3. complete the square on the left side of the equation and balance this by adding the same number to the right side of the equation
(1.67/2)² = 0.84² = 0.71 
x² - 1.67x + 0.71 = -0.67 + 0.71
x² - 1.67x + 0.71 = 0.04
(x - 0.71)² = 0.04

Step 4. take the square root of each side of the equation
x - 0.71 = 0.20
x = 0.20 + 0.71
x = 0.91

0